2011
DOI: 10.1007/s10560-011-0245-x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Motivations of Cutting Behavior Among Sexual Minority Youth

Abstract: This aim of this study is to examine predictors of specific motivations for engaging in cutting behavior among a community sample of sexual minority youth. The study involved secondary analysis of data collected by a communitybased organization serving lesbian, gay, bisexual, and transgender (LGBT) youth and their allies. Descriptive and logistic regression analyses were conducted using a final sample of 131 sexual minority youth ages 13-24. Analyses indicate that cutting occurs at high rates among sexual mino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…The most important functions of self-injury were to suppress/avoid negative thoughts/images, negative feelings, and suicidal thoughts, followed by punishing oneself. This is consistent with other research that has found that emotion regulation and selfpunishment are often described as the most important functions of NSSI in general populations [8,9] [20], in the only study investigating NSSI in a sample that included trans participants, found that overall in LGBT people, emotional release was the most important function of NSSI, followed by stimulation and self-hate. However, the study only included 13 self-diagnosed trans individuals.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The most important functions of self-injury were to suppress/avoid negative thoughts/images, negative feelings, and suicidal thoughts, followed by punishing oneself. This is consistent with other research that has found that emotion regulation and selfpunishment are often described as the most important functions of NSSI in general populations [8,9] [20], in the only study investigating NSSI in a sample that included trans participants, found that overall in LGBT people, emotional release was the most important function of NSSI, followed by stimulation and self-hate. However, the study only included 13 self-diagnosed trans individuals.…”
Section: Discussionsupporting
confidence: 91%
“…For example, Nickels et al. [20], in the only study investigating NSSI in a sample that included trans participants, found that overall in LGBT people, emotional release was the most important function of NSSI, followed by stimulation and self‐hate. However, the study only included 13 self‐diagnosed trans individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further analysis of the survey data from the subgroup of participants who reported cutting ( n = 131) investigated motivations for this behaviour (Nickels et al . ). The most frequently reported motivation for cutting was to experience ‘an emotional release’ (72·5% of participants) and the second most commonly reported motivation for cutting was ‘in order to feel something’ (51·9%).…”
Section: Resultsmentioning
confidence: 97%